Strategi Peningkatan Kesejahteraan Petani di Kabupaten Temanggung: Sebuah Analisis SWOT - Alif Waluyo; Fahri Ali Ahzar; Yulfan Arif Nurohman (University of Jember, 2023)
Tobacco has been a leading crop for farmers in Temanggung Regency for decades, but since the 2000s tobacco yields have not been able to improve farmers' welfare. The economic welfare of tobacco farmers is increasingly disappearing, even though farmers are faced with the problem of basic needs that cannot be delayed. This research needs to be conducted considering the economic condition of tobacco farmers which continues to decline in Temanggung Regency from time to time. The purpose of the research was to find the right strategy to improve the welfare and economy of tobacco farmers in Temanggung Regency. This research uses an analytical descriptive approach that uses primary and secondary data. Primary data was obtained through interviews, observations, focus group discussions, and documentation. Secondary data was obtained from books and journals. The data obtained was used to develop strategies based on SWOT analysis. The results of the SWOT analysis compiled obtained diversification strategies include shortening the dried tobacco marketing chain, increasing tobacco festivals in collaboration with tourist villages, making tobacco-based vegetable pesticides, and establishing tobacco cooperatives or farmer groups capable of managing the sale of dried tobacco from farmers.